(untitled) (PANGEEA, 2025)
Nicolae Iorga said ”It is not enough for a country to birth talents; she must know how to keep them alive.” (Scrieri despre Arta) The wonderful world of popular traditions and customs is one that still exists, but which is marked by the passage of time, oblivion, aging and, paradoxically, renewal and change. It is obvious that many of the customs are lost due to their meaning disappearing, that the traditions suffer from an aging phenomenon and eventually they disappear. It’s the law of nature that life goes on, the new replaces the old, and people live the present with a view for the future. A thought about the past, however, can do no harm to anyone, but the contrary; we must remember that our ancestors have succeeded, over the centuries, to ensure the most important thing - the continuity of life within a framework of traditions, knowledge and customs passed down from generation to generation.